Ensuring Early Childhood Children’s Right to a Safe and Healthy Family Life - Lebedzinskiene, Lijana; Bilbokaitė-Skiauterienė, Ieva (Jaunųjų mokslininkų darbai, 2022)
The theoretical insights into the problem under analysis allow us to state that, in the context of constant changes in social life, people’s thinking and habits as well as the problem of protecting children’s rights in the family remain topical and in need of further research. It is therefore appropriate to explore in more depth how parents perceive their responsibilities and opportunities in guaranteeing the right of the early child to grow up healthy and safe, what problems they face and how they deal with them. The aim of the study is to reveal parents’ views on the right of the early years’ child to a safe and healthy family life. The study is based on the following conceptual frameworks: the Social Construction of Reality Theory (Berger, Luckmann, 1999) and the Child-Centred Educational Paradigm (Dewey, 1961; Juodaitytė, 2003; Monkevičienė, 2008). The qualitative approach was used in the study, the choice of which was determined by the specificity of the analyzed problem and personal preference for qualitative research. The following research methods were employed: the analysis of scientific literature, normative documents containing information about the research object; semi-standardized interview. The content analysis method was used to analyse the research data. Seven parents of early childhood children participated in the study. On the basis of the theoretical insights and the results of the qualitative research, it can be concluded that the parents who participated in the study are aware of their responsibility and potential in ensuring the child’s right to grow up healthy and safe, and they understand the significance of this right for the child’s personality. The results obtained provide an opportunity for further analysis of the right of the early childhood child to grow up healthy and safe, and to gain insight into the parents’ experiences in this aspect. Parents aim to raise their children’s awareness of the importance of a healthy lifestyle, proper nutrition, physical activity, participation in their children’s lives, creating a sense of security and ensuring a supportive home environment.